PERTUMBUHAN CACING SUTERA PADA MEDIA KOTORAN PUYUH DAN AMPAS TAHU TERFERMENTASI SERTA TEPUNG TAPIOKA DENGAN KOMPOSISI BERBEDA - Muhammad Fachri; mirna fitrani; yulisman . (Universitas Sriwijaya, 2016)
ABSTRACT Silk worm is one of natural feed with high nutrien content. The supply of silk worm is still rely on nature, therefore needs to be cultured. The aim of this research was to know the growth of silk worm that cultured on combination media of quail manure and tofu waste fermented and tapioca flour. This research conducted since March until May 2015 in Laboratorium Dasar Perikanan, Aquaculture Program Study, Faculty of Agriculture, Sriwijaya University. The research method used Completely Randomized Design (CRD) with three treatments and three replications : (Treatment A : 50% fermented quail manure, 35% fermented tofu waste and 15% tapioca flour, Treatment B : 50% fermented quail manure, 25% fermented tofu waste and 25% tapioca flour, Treatment C : 50% fermented quail manure, 15% fermented tofu waste and 35% tapioca flour). The fermented quail manure, fermented tofu waste and tapioca flour were entered to container base on composition treatment with water flow 525 mL/min. Silk worm were put on media for 42 days. The results showed that culture of silk worm used fermented quail manure, fermented tofu waste and tapioca flour gives significantly effect (P<0,05) on biomass production, population and nutrition content of silk worm. The treatment B reached the fastest time of population and the highest of population, biomass also nutrien contain. Based on the results, the culture of silk worm use quail manure and tofu waste fermented and tapioca flour could increase biomass, population and nutrition content of silk worm. Â Keywords : tofu waste, fermentation, quail manure, growth of silk worm, tapioca flour